PENGARUH PAPER QUILLING TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK - Arina Puspitasari (Universitas Negeri Makassar, 2021)
The purpose of this study was to determine the effect of paper quilling on the fine motor skills of children aged 5-6 years. This research approach is quantitative with the type of pre-experimental research and the research design of one group pretest-posttest design. This study took place at ABA II Kindergarten, Arallae, Bone Regency, with the subject of research on the effect of paper quilling activities on fine motor skills consisting of 12 children as research samples. Data collection techniques used are observation, treatment test and documentation. The results of the analysis showed that there were significant changes in the fine motor skills of children before and after being given paper quilling activities, based on the paired sample test, the Sig value was obtained. (2-tailed) 0.000 < 0.05, it can be concluded that there is an influence given by paper quilling activities on the fine motor skills of children aged 5-6 years. For further researchers in examining aspects of child development, it can be simulated with paper quilling activities.